Áreas de refúgio: ressaca pacoval sob perspectiva urbano/social - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2015)
This work consists in a social and urban study of the wetlands in the municipality of Macapá, State of Amapá, with main focus on Pacoval wetland, located in the north of the city. This research presents the main stages of spatial development Macapá and how these facts contributed to the occupation of these areas, as well as other factors such as lack of public policies and negligence in the application of urban instruments that in principle should conduct the urban growth of the city. The relevance of this research is justified by the great importance that these areas have for the state of the ecosystem, since the disorderly occupation can generate a range of social and economic negative consequences as well as environmental impacts. Through these occupations have been raised main points which are the focus of this research, they are: urban planning and public management instrument, socio-spatial segregation, use and land use and quality of life for residents of these areas. The objective of this research is to make a social and environmental research for the purpose of improving the quality of life of residents of that wetland addition to contextualize the points raised here to propose a solution through intervention with social and environmental responsibility, to minimize the impact of the occupation.
Keywords: Arquitetura - Planejamento urbano; Intervenção urbana; Crescimento desordenado - Arquitetura; Áreas de ressaca; CNPQ::CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO